Serum procalcitonin and cerebrospinal fluid cytokines level in children with meningitis - Taskin, E; Turgut, M; Kilic, M; Akbulut, H; Aygun, AD (Wiley, 2004)
AIMS: To determine the level of serum procalcitonin and cerebrospinal fluid cytokines in children with bacterial or viral meningitis and to document the use of these parameters in differential diagnosis. Results: Before the start of antibiotic treatment, serum procalcitonin and tumor necrosis factor alpha levels were found to be higher in acute bacterial meningitis compared with viral meningitis and with the control group. Similarly, cerebrospinal fluid interleukin-6 levels were found to be significantly higher in children with acute bacterial meningitis compared with viral meningitis. However, no significant difference was determined between groups in respect to the cerebrospinal fluid interleukin-8 level. Conclusion: Serum procalcitonin and cerebrospinal fluid tumor necrosis factor alpha levels can be used in the early diagnosis of bacterial meningitis. Similarly, they may be useful adjuncts in differential diagnosis of bacterial and viral meningitis.
Keywords: meningitis; procalcitonin; tumor necrosis factor alpha; interleukin-6; interleukin-8; children